Association between pregnancy and adnexal torsion: A population-based, matched case-control study. Issue 24 (June 2016) - Yuk, Jin-Sung; Shin, Ji-Yeon; Park, Won I.; Kim, Dae Woon; Shin, Jung Whan; Lee, Jung Hun
Abstract : Abstract: The purpose of this study was to determine the effect of pregnancy on adnexal torsion (AT). We conducted a matched case-control study using the Korean Health Insurance Review and Assessment Service–National Inpatients Sample (HIRA-NIS) from 2009 to 2011. AT patients were defined as women with both a diagnostic code (N835) and a surgical code for AT. The AT patients were randomly matched 1:4 with women without AT by age and year of claim. In total, 545 AT cases and 2180 controls were enrolled from a total of 1, 843, 451 women. After adjustment for such covariates as age, pregnancy was found to be associated with a lower rate of AT (adjusted odds ratio 0.314, 95% confidence interval [CI] 0.237–0.416, P value <0.01) and ovarian hyperstimulation syndrome was associated with a higher rate of AT (adjusted odds ratio 20.091, 95% CI 3.607–111.908, P value <0.01). We found that pregnancy is a negative risk factor for AT. However, a further study is needed to elucidate the mechanisms underlying these results.